2008
DOI: 10.1530/rep-07-0453
|View full text |Cite
|
Sign up to set email alerts
|

Expression of genes involved in prostaglandin E2 and progesterone production in bovine cumulus–oocyte complexes during in vitro maturation and fertilization

Abstract: Prostaglandin E 2 (PGE 2 ) and progesterone appear to be critical mediators of cumulus expansion and the resumption of oocyte meiosis. The aim of this study was to identify the types of prostaglandin E synthase (PTGES) expressed in the bovine cumulus-oocyte complex (COC), to characterize their temporal expression during the periconceptional interval using an in vitro model of maturation (IVM) and fertilization (IVF), and to compare their expression with the level of steroidogenic gene expression. Real-time RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 59 publications
5
40
0
1
Order By: Relevance
“…Among the three PTGES isoforms, only PTGES1 was responsive to Gn stimulation during maturation. This finding is in agreement with a previous report where only PTGES1 of the three isoforms of PTGES detected was found to increase during bovine oocyte maturation, paralleling the induction of PTGS2 enzyme (Nuttinck et al, 2008). This is not only observed in COC, as it was shown that while all PTGES isoforms were expressed in the bovine oviduct (Gauvreau et al, 2010) and endometrium , PTGES1 was reported to be the main enzyme associated with PGE 2 production .…”
Section: Discussionsupporting
confidence: 93%
“…Among the three PTGES isoforms, only PTGES1 was responsive to Gn stimulation during maturation. This finding is in agreement with a previous report where only PTGES1 of the three isoforms of PTGES detected was found to increase during bovine oocyte maturation, paralleling the induction of PTGS2 enzyme (Nuttinck et al, 2008). This is not only observed in COC, as it was shown that while all PTGES isoforms were expressed in the bovine oviduct (Gauvreau et al, 2010) and endometrium , PTGES1 was reported to be the main enzyme associated with PGE 2 production .…”
Section: Discussionsupporting
confidence: 93%
“…Inhibition of PGE production using PTGS2 inhibitors was found to attenuate cumulus expansion and GVBD of mouse oocytes [17][18][19]43]. In cattle, the mRNAs of PTGS2 and PGE 2 receptors (PTGER2 and PTGER3) were expressed in COCs, and PGE 2 was found to induce moderate cumulus cell expansion [41,44,45], which suggests that PGs may have an important role in oocyte maturation. In the studies presented here, inhibition of PTGS2 by NS-398 resulted in a significant reduction in oocyte nuclear maturation.…”
Section: Discussionmentioning
confidence: 96%
“…It acts through G-protein coupled receptors (PTGER) on cumulus cells (Calder et al 2001). Linoleic acid influences oocyte development mRNA for PTGS2 and PGE 2 receptors (PTGER2 and PTGER3) are expressed in bovine COCs (Nuttinck et al 2002(Nuttinck et al , 2008, and PGE 2 was also shown to induce moderate expansion of cumulus cells (Calder et al 2001). This suggests that PGE may have a role in oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%